Effect of White Champa Leaf Extract (Plumeria acuminata) on White Fly Eclosion (Aleurolobus barodensis Maskell, Hemiptera; Aleyrodidae) - Vivin Diana Putri; Etik M Achadian (Indonesian Sugar Research Journal, 2021)
The white fly explosion might be occurred on the flooded fields and lack of nitrogen fertilizer. Some control methods have to be conducted to prevent further losses. The use of biopesticide was known to be easier, cheaper and environmental friendly control methods. Therefore the aim of this experiment was determining the effect of white champa leaf extract (Plumeria acuminata) as a biopesticide on sugarcane white fly eclosion (Aleurolobus barodensis). Experiment was conducted in the laboratory, using a completely randomized design with 6 treatments of P. acuminata leaf extract concentrations, that were 0% (control), 10%, 20%, 30%, 40% and 50%, and was replicated 4 times. The results showed that P. acuminata leaf extract could be used to control sugarcane white fly. The effective leaf extract concentration was 40%. The results also proved that P. acuminata leaf extract killed the white fly pupae instead of delaying their eclosion.